Hydrogel-Based Novel Biomaterials: Achievements and Prospects (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue highlights recent advancements in the synthesis and processing of hydrogel-based biomaterials. It presents cutting-edge research on various topics, including the production of hydrogels (selection and influence of raw materials/additives, use of unconventional sterilization methods, etc.) and their in vitro and in vivo characterization. The focus spans biotechnological applications, such as enzyme immobilization, scaffolds, tissue engineering, and biofabrication, as well as therapeutic applications like ocular treatments, local anti-cancer therapies, and topical or transdermal drug delivery.These contributions underscore the pivotal role of hydrogels in developing sophisticated medical treatments and devices, paving the way for personalized medicine, improved patient outcomes, and innovative solutions to complex medical challenges. The Editorial summarizes the diverse approaches presented and explores future possibilities.